Peran Kepala Sekolah dalam Pendidikan Multikultural pada Pengembangan Sikap Toleransi - Siregar, Siti Masdelina; Nasution, Inom (MODELING: Jurnal Program Studi PGMI, 2024)
In an educational context, multiculturalism focuses on developing an inclusive curriculum and learning environment, where students from diverse cultural backgrounds feel respected and supported. The aim is to build deeper intercultural understanding, reduce prejudice, and promote tolerance and social cohesion. This research aims to analyze the role of school principals in multicultural education and its impact on developing attitudes of tolerance among students. This research was conducted at Budisatrya Medan Tembung Private Middle School with the research method used was a qualitative approach. There were four participants who were selected and willing to become participants in this research, namely the school principal, deputy head of student affairs, Muslim and non-Muslim students. The data collection process was carried out through digital audio-visual recorded interviews conducted verbally and face-to-face by researchers and participants with the aim of getting more in-depth information about how and what influence the leadership and policies of the principal at Budisatrya Private Middle School in Medan. The research results show that the active involvement of school principals in multicultural education significantly contributes to increasing students' attitudes of tolerance, reducing prejudice, and encouraging the creation of a school culture of harmony and mutual respect. These findings emphasize the importance of the role of school principals as agents of change in advancing multicultural education and forming a younger generation that is more open and tolerant of differences. Abstrak Dalam konteks pendidikan, multikulturalisme menitikberatkan pada pengembangan kurikulum dan lingkungan belajar yang inklusif, di mana siswa dari beragam latar belakang budaya merasa dihormati dan didukung. Tujuannya adalah untuk membangun pemahaman antarbudaya yang lebih mendalam, mengurangi prasangka, serta mempromosikan toleransi dan kohesi sosial. Penelitian ini bertujuan untuk menganalisis peran kepala sekolah dalam pendidikan multikultural dan dampaknya terhadap pengembangan sikap toleransi di kalangan siswa. Penelitian ini dilakukan di SMP Swasta Budisatrya Medan Tembung. Metode penelitian yang digunakan adalah pendekatan kualitatif. Ada empat partisipan yang dipilih dan bersedia menjadi partisipan dalam penelitian ini yaitu kepala sekolah, wakil kepala bagian kesiswaan, siswa yang beragama islam dan non islam. Proses pengumpulan data dilakukan melalui wawancara rekaman audio visual digital yang dilakukan secara lisan dan tatap muka oleh peneliti dan partisipan yang mana bertujuan agar mendapat informasi lebih dalam mengenai bagaimana dan apa pengaruh kepemimpinan dan kebijakan kepala sekolah di SMP Swasta Budisatrya Medan. Hasil penelitian menunjukkan bahwa kepala sekolah terlibat dalam pendidikan multikultural secara aktif dan secara signifikan berkontribusi pada peningkatan sikap toleransi siswa, mengurangi prasangka, dan mendorong terciptanya budaya sekolah yang harmonis dan saling menghormati. Temuan ini menekankan pentingnya peran kepala sekolah sebagai agen perubahan dalam memajukan pendidikan multikultural dan membentuk generasi muda yang lebih terbuka dan toleran terhadap perbedaan.